PERANCANGAN LOGO DAN MEDIA PROMOSI FILIA BUSANA KOTA SOLOK - DIAMER HADI KURNIA, Eliya Pebriyeni, S.Pd., M.Sn Ishakawi, S.Pd., M.Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Filia Busana is a home-based boutique that sells a variety of womensclothing, a specially teenagers shoes. Filia Busanas products offered can be said in terms of price and in terms of quality luxury. But in reality, not many people are coming to Filia Clothing for shopping. This is due not many people in Solok as consumers aware of the existence of Filia Busana for newly established on March 18, 2014. As a new company that is relatively small and do not yet have a company logo, moreover signpost yet have a name, would be very difficult for Filia Busana to expand its business. Therefore, Filia Busana is in need of a logo company that serves as a symbol of a differentiator with other companies. Designed logo applied to the various media support such as neon box, xbanner, shopping bags, calendars, note book, price tags, pins, and stickers. Analyze methods used in the data, the authors use the theory of Harold Laswell